Interfaith Marriage in Bangladesh: A Comparative Analysis of Past and Present Trends and Sociocultural Aspects - Md Amirul Islam; Mst. Baly Khatun; Murshida Khatun (HISTORICAL: Journal of History and Social Sciences, 2024)
This study examines the dynamics of interfaith marriage in Bangladesh, many customs and rituals, different religious society views, and marriage reviews, offering a comparative analysis of past and present trends and exploring the sociocultural aspects surrounding these unions, with specific consideration given to the influence of the Marriage Act of 1872. The objectives of the study aim to the historical evolution of interfaith marriages, analyze the sociocultural factors influencing their occurrence, and assess the impact of the Marriage Act of 1872 on regulating such unions. The research methodology involves a comprehensive review of the literature, an examination of historical data conducted with a qualitative approach. The findings suggest a noticeable increase in interfaith marriages, driven by urbanization, globalization, and changing religious perspectives. Despite legal provisions, societal and cultural barriers persist, presenting challenges for interfaith couples. The study concludes by the importance of promoting awareness, understanding, and acceptance of interfaith marriages in Bangladesh and proposing legal reforms and educational initiatives a more inclusive and harmonious society.